Rapid Identification of Fermentation Spoilage Microbes Using Molecular Beacons and a Two-Step Direct DNA Amplification Protocol. (2nd July 2020) - Shaw, Benjamin; Reekers, Corrine; Fenske, William; Fugate, Dylan; Brock, Martin; Fredericks, Jamie
Abstract: Bacterial contamination is a long-standing problem in the brewing and distilling industry. Extant approaches in measuring contamination levels, or for measuring specific microbes, is either slow or expensive. A very rapid (< 1 hr) DNA method using PCR coupled with a fluorescent molecular beacon, showing a sensitivity able to detect levels of a common contaminant ( L. delbrueckii ), well before sensory signals are triggered, is described. The approach is highly discriminatory, able to differentiate among contaminating strains within a genus, and even in the presence of a considerable excess of desirable strains. The approach implies ways to determine entry points for contamination to help ameliorate the problem and could save a considerable amount of time, resources, and income for the manufacturer.